25th annual research day: scientific proceedings - Colorado State University. College of Veterinary Medicine and Biomedical Sciences, publisher (Colorado State University. Libraries, 2024)
Our 25th annual Research Day held on January 26-27, 2024 showcases the work of nearly 200 aspiring scientists in Colorado State University's College of Veterinary Medicine and Biomedical Sciences. The event gives our rising stars vital experience presenting their research findings to a scientific audience through poster displays and talks. The day also provides young researchers with an avenue for feedback to help them develop ideas that, in many cases, will become lifelong scientific pursuits. The research projects on display are sponsored by companies, foundations, and institutions concerned with improving human, animal, and environmental well-being. Thank you for supporting and engaging with our presenters – undergraduate students, graduate students, veterinary residents, and post doctoral fellows – as they pursue research that will improve the health of animals, people, and the planet!

Includes the Zoetis Research Excellence Award winner, program of oral and poster presentations and selected presentation abstracts.
Scientific proceedings: 25th annual research day
2024 CVMBS research day
Keywords: Veterinary medicine -- Congresses; Veterinary medicine -- Research -- Congresses